LRP-1 links post-translational modifications to efficient presentation of celiac disease-specific T cell antigens. Issue 1 (19th January 2023) - Loppinet, Elise; Besser, Harrison A.; Sewa, Agnele Sylvia; Yang, Fu-Chen; Jabri, Bana; Khosla, Chaitan
Summary: Celiac disease (CeD) is an autoimmune disorder in which gluten-derived antigens trigger inflammation. Antigenic peptides must undergo site-specific deamidation to be presentable to CD4 + T cells in an HLA-DQ2 or -DQ8 restricted manner. While the biochemical basis for this post-translational modification is understood, its localization in the patient's intestine remains unknown. Here, we describe a mechanism by which gluten peptides undergo deamidation and concentration in the lysosomes of antigen-presenting cells, explaining how the concentration of gluten peptides necessary to elicit an inflammatory response in CeD patients is achieved. A ternary complex forms between a gluten peptide, transglutaminase-2 (TG2), and ubiquitous plasma protein α2 -macroglobulin, and is endocytosed by LRP-1. The covalent TG2-peptide adduct undergoes endolysosomal decoupling, yielding the expected deamidated epitope. Our findings invoke a pathogenic role for dendritic cells and/or macrophages in CeD and implicate TG2 in the lysosomal clearance of unwanted self and foreign extracellular proteins. Graphical abstract: Highlights: Endocytosis of gluten antigens depends on transglutaminase-2 and α2 -macroglobulin LRP-1 mediates uptake, causing lysosomal concentration of deamidated gluten peptides Peptidomimetic active TG2 probes allow tracking of TG2 through the endolysosome Antigens taken up through this pathway are presented on MHC-II in a DQ2 restricted way Abstract : Loppinet et al. demonstrate that gluten peptides bound to TG2 undergo LRP-1-mediated endocytosis in the presence of α2 -macroglobulin. Deamidated gluten peptides are then concentrated in the endolysosomal system and efficiently displayed on MHC-II in HLA-DQ2-expressing cells. This invokes a pathogenic role for macrophages and dendritic cells in celiac disease.